Modelling ingrowth in mediterranean pine forests: A case study from scots pine (Pinus sylvestris L.) and mediterranean maritime pine (Pinus pinaster AIT9 stands in Spain - Bravo, F.=700 1 Pando, V.; Ordoñez, C.; Lizarralde, I.
(Es, En)
Ilus., 72 ref.
Keywords: PINUS SYLVESTRIS; PINUS PINASTER; PESO; BIOMASA; REGENERACION; INVENTARIOS FORESTALES; PARCELAS; ESPAÑA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES